2015
DOI: 10.1002/anie.201502475
|View full text |Cite
|
Sign up to set email alerts
|

The Radiative Lifetime in Near‐IR‐Luminescent Ytterbium Cryptates: The Key to Extremely High Quantum Yields

Abstract: A powerful strategy for the improvement of near-IR lanthanoid luminescence has been successfully employed for the first time, which involves the rational and deliberate shortening of the radiative luminescence lifetimes τ(rad) in molecular ytterbium complexes. In this context, the bidentate chelating unit 2,2'-bipyridine-N,N'-dioxide has been identified as being responsible for decreasing τ(rad) substantially in macrobicyclic Yb cryptates. This strategy, when combined with conventional approaches, yields unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 18 publications
9
76
0
Order By: Relevance
“…Sm III or Yb III ) are especially sensitive towards nonradiative deactivation processes caused by multiphonon quenching. Past studies have shown that deuterated derivatives of the cryptates have a special ability to protect this group of lanthanoids against nonradiative deactivation processes, leading to extraordinarily long luminescence lifetimes of the corresponding Yb III and Sm III complexes in deuterated solvents ,. In the case of Sm III this also leads to very promising conditions for the observance of CPL.…”
Section: Introductionsupporting
confidence: 83%
“…Sm III or Yb III ) are especially sensitive towards nonradiative deactivation processes caused by multiphonon quenching. Past studies have shown that deuterated derivatives of the cryptates have a special ability to protect this group of lanthanoids against nonradiative deactivation processes, leading to extraordinarily long luminescence lifetimes of the corresponding Yb III and Sm III complexes in deuterated solvents ,. In the case of Sm III this also leads to very promising conditions for the observance of CPL.…”
Section: Introductionsupporting
confidence: 83%
“…6,17a Thus we chose [D 18 ]-3-Yb as an example to measure τ rad in CD 2 Cl 2 because of its good solubility up to 10 –2 M (ESI Fig. S92†).…”
Section: Resultsmentioning
confidence: 99%
“…However, the respective metal ion based emission lifetimes were also successfully determined for the Dy 3+ , Pr 3+ , Ho 3+ , Tm 3+ , and Yb 3+ products (Table 1), which are also close to the values presented in the literature. [13,[58][59][60][61][62][63][64][65][66][67][68][69] Emission lifetimes were determined at low temperature as well; detailed data can be found in the SI. The most significant changes in emission lifetimes between r.t. and 77 K can be observed for complexes of 2-Tb and 2-Dy, for which an increase by more than 5 times compared to r.t. decay times was observed at 77 K (2-Tb: 2249(2) μs, 2-Dy: 14.0(3) μs).…”
Section: Photophysical Propertiesmentioning
confidence: 99%